Penyebab Menurunnya Kinerja Mesin Pendingin di MV. Vancouver - Siregar, Muhammad Sapril; Rafi Zidane Shevchenko; Albert Wiweko (PT. PENERBIT TIGA MUTIARA, 2023)
A cooling machine or commonly called an Air Conditioner (AC) is a system of auxiliary machines that can create cool temperatures in certain rooms so that workers on ships feel comfortable. Cooling machines are used to regulate and manage air quality which are includes air circulation, air conditioning, air hygiene standards and air purification. There are several main components in the cooling machine, namely the Compressor, Condenser, Expansion Valve, Evaporator. Each of these important components has different functions and ways of operating, but are connected to each other so that the cooling machine can function. The purpose of the author making this final project is to determine the performance of the cooling system, factors that reduce the performance of the cooling machine, as well as repair and maintenance efforts so that the cooling machine can return to normal operation. This research was conducted on the MV. Vancouver by using a qualitative approach. The author conducted direct observations as well as in-depth interviews and documentation studies when conducting research. The results of the author's research found that the main factor causing the decline in the performance of the cooling machine was the appearance of sparks on the evaporator and coil pipe caused by interference with the filter dryer so that it inhibits heat absorption and the evaporator cannot evaporate the refrigerant optimally. The impact caused by the less than optimal operation of the cooling machine in the Engine Room Workshop MV. Vancouver was an unstable room temperature making the crew feel uncomfortable while working or resting.